Voice-related quality of life after total laryngectomy: a scoping review of recent evidence - Tatiana Pourliaka; Efcharis Panagopoulou; Vassiliki Siafaka (Health and Quality of Life Outcomes)
Abstract Background Laryngeal cancer often leads to total laryngectomy (TL), which results in the loss of natural voice, necessitates voice rehabilitation and affects the individuals Quality of Life (QoL). Despite advancements in treatment, Voice-Related QoL (VRQoL) post TL remains a neglected area in the field of rehabilitation. This study seeks to fill this gap by evaluating though a scoping review the impacts of TL on patients’ voice-related QoL. Methods A scoping review was conducted to assess the impact of total laryngectomy (TL) on voice-related quality of life (VRQoL). The search was performed across various electronic databases—PubMed, Scopus, Embase, Cohrane Library, Google scholar and Web of Science— using a broad set of keywords to capture studies addressing total laryngectomy and voice-related quality of life (VRQoL). Articles were screened using predefined inclusion and exclusion criteria, focusing on studies that directly addressed TL and VRQoL outcomes. Results A total of eleven papers were finally selected to respond to the research question. The review indicates that TL significantly impacts VRQoL. Common issues included difficulties with communication in noisy environments, social interactions, anxiety about being understood, and physical challenges related to voice production. These difficulties were reflected in lower scores on various assessment tools. Patients reported declines in socio-emotional functioning and faced challenges in physical activities requiring voice use. Conclusions This scoping review highlights the profound impact of TL on patients’ voice-related QoL. Despite advances in surgical techniques and rehabilitation methods, patients continue to experience significant challenges in communication and social integration, which are crucial components of overall well-being. The persistent lower scores across various QoL assessment tools underscore the necessity for enhanced supportive care and innovative rehabilitation strategies tailored to the specific needs of this population.